ASPECTS OF USING MODERN PEDAGOGICAL TECHNOLOGIES IN PHYSICAL EDUCATION AND SPORTS LESSONS - Sotvoldiyev Qodirjon Rahimjonovich; Mirzabayev Xurshed Rustamovich (Galaxy International Interdisciplinary Research Journal, 2024)
In the article physical education and sports in their classes modern pedagogical from technologies of use importance , outlook and thinking scope harvest to do , physical , spiritual and moral adjectives formation according to some recommendations given discussion done